Boron-doped Sb/SbO2@rGO composites with tunable components and enlarged lattice spacing for high-rate sodium-ion batteries. (28th May 2021) - Liu, Jin-Hua; Li, Yan-Fei; Shi, Yan-Hong; Guo, Jin-Zhi; Yang, Jin; Wu, Xing-Long; Zhang, Jing-Ping; Hu, Wei; Sun, Hai-Zhu
Abstract: Antimony (Sb) and its oxides, as promising electrode materials, have attracted much attention because of their low cost, environmental friendliness, and high theoretical capacity. Herein, boron doped flower-cluster-like Sb/SbO2 @reduced graphene oxide (rGO) composites are synthesized for use as sodium-ion battery anode materials using a solvothermal strategy. The contents of Sb and antimony oxide (SbO2 ) are controlled by adding different contents of NaBH4 . Meanwhile, the introduction of NaBH4 successfully realizes boron doping and enlarges the lattice spacing of the SbO2, improving its conductivity and Na + transport. As a result, optimal Sb/SbO2 @rGO-10 composites display a desirable capacity of 346 mAh g −1 at 50 mA g −1 after 100 cycles with a capacity retention of 106%. Even at high current densities, a capacity of 236 mAh g −1 is achieved, demonstrating a satisfactory rate capacity. Moreover, the Sb/SbO2 @rGO-10 electrode shows satisfactory Na storage performance at low temperatures. In addition, sodium-ion full cells are assembled using an Sb/SbO2 @rGO-10 anode and a Na3 V2 (PO4 )2 O2 F cathode, with which a satisfactory electrochemical performance of 102 mAh g −1 after 50 cycles at 50 mA g −1 is achieved, showing their high practical potential.